OUTCOME OF OPEN CARPAL TUNNEL RELEASE SURGERY - Khan, Abdul Aziz; Ali, Haider; Ali, Kishwar; Muhammad, Gul; Rashid, Bushra; Gul, Nasim; Zadran, Khalid Khan; Mushtaq, Mohammad; Saboor, Abdus; Ali, Sajjad; et al. (Journal of Ayub Medical College Abbottabad, 2015)
Background: Carpel tunnel syndrome is a common compression neuropathy of the median nerve causing pain, numbness and functional dysfunction of the hand. Among the available treatments, surgical release of the nerve is the most effective and acceptable treatment option. The aim of this study was to see the outcomes of surgical release of carpel tunnel using open technique. Methods: This descriptive case series was conducted at the Department of neurosurgery, Ayub Teaching Hospital Abbottabad from April 2013 to March 2014. One hundred consecutive patients with carpel tunnel syndrome were included who underwent open carpel tunnel release surgery. They were followed up at 1, 3 and 6 months. Residual pain, numbness and functional improvement of the hand were the main outcome measures. Results: Out of 100 patients, 19 were males. The age ranged from 32 to 50 years with a mean of 39.29±3.99 years. The duration of symptoms was from 5 to 24 months. In the entire series patient functional outcome and satisfaction was 82% at 1 month, 94% at 3 months and 97% at 6 months. 18% patient had residual pain at 1 month post-operative follow-up, 6% at 3 months and 3% at 6 month follow-up. Conclusion: Open carpel tunnel release surgery is an effective procedure for compression neuropathy of the median nerve. It should be offered to all patients with moderate to severe pain and functional disability related to carpel tunnel syndrome.